DETERMINANTS THAT INFLUENCE THE INTEREST IN INVESTING IN STOCK STUDENTS FACULTY OF ECONOMICS AND BUSINESS UNIVERSITY OF ATMA JAYA MAKASSAR - Marselinus Asri; Jocelyn Odelia Josephine; Ana Mardiana (Contemporary Journal on Business and Accounting, 2021)
Purpose – The purpose of this study is to analyze the effect of minimum investment fund, return, risk, and environment on interest in investing shares of students of the faculty of economics and business Atma Jaya Makassar University. Design/methodology/approach – The type of research used in this research is causality research. This research used purposive sampling method in sampling technique. The sample used in this study are 5th and 7th students of accounting department, faculty of economics and business Atma Jaya Makassar University. So that the total sample obtained is 144 respondents. Findings – The result of this study indicate that minimum investment fund, return, and environment have a positive and significant effect on interest in investing shares of students of the faculty of economics and business Atma Jaya Makassar University. On the other hand, risk is not significant and has a negative effect on interest in investing shares of students of the faculty of economics and business Atma Jaya Makassar University. Originality – The data collection method used in this study was a survey in the form of a questionnaire. Keywords: Environment, Interest In Investing Shares, Minimum Investment Fund, Return, and Risk Paper Type Research Result